The Effects of Premium, Claim, and Invesment Yield on the Earning of Islamic Insurance Companies for the 2023 – 2024 Period - Febrian, Mohammad Rizky; Widiyanti, Dwi Retno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the impact of premiums, claims, and investment returns on the profitability of Islamic insurance companies in Indonesia during the period 2023-2024. The method used is quantitative by utilizing secondary data taken from the financial statements of Islamic insurance companies registered with the Otoritas Jasa Keuangan (OJK). The analysis technique applied is panel data analysis, which combines cross-section and time series data. It is hoped that the results of this study can provide deeper insight into the factors that affect the profitability of Islamic insurance companies and provide practical implications for industry players and regulators in formulating more effective and efficient management strategies.